Correction: Retraction: Tanshinone IIA Inhibits HIF-1α and VEGF Expression in Breast Cancer Cells via mTOR/p70S6K/RPS6/4E-BP1 Signaling Pathway. - PLOS One Editors (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0321151.].